2018
DOI: 10.1186/s41043-018-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and metabolic risk factors for non-communicable diseases in a university undergraduate population

Abstract: BackgroundUnhealthy dietary patterns are associated with metabolic changes and increased risk of non-communicable diseases (NCDs), but these associations have not been investigated in representative populations of university undergraduates in low-to-middle income countries (LMICs).MethodsThis study was conducted in the three universities in Lagos State, Nigeria to assess the dietary pattern and metabolic risk factors of NCDs among university undergraduate population. Multistage sampling technique was used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
76
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 38 publications
(40 reference statements)
8
76
3
3
Order By: Relevance
“…As part of an unhealthy dietary pattern, this may have an effect on increased blood sugar, LDL-cholesterol and triglycerides. Thus, poor diet contributes to the occurrence of a cluster of disorders known as the metabolic syndrome: abdominal obesity, hypertension, dyslipidemia, and disturbed metabolism of glucose or insulin [42]. The presence of the metabolic syndrome increases the risk of developing NCDs such as cardiovascular diseases, diabetes, chronic respiratory diseases, and cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…As part of an unhealthy dietary pattern, this may have an effect on increased blood sugar, LDL-cholesterol and triglycerides. Thus, poor diet contributes to the occurrence of a cluster of disorders known as the metabolic syndrome: abdominal obesity, hypertension, dyslipidemia, and disturbed metabolism of glucose or insulin [42]. The presence of the metabolic syndrome increases the risk of developing NCDs such as cardiovascular diseases, diabetes, chronic respiratory diseases, and cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is recommended to include five portions of fruits and vegetables in daily food rations [ 39 ]. From randomized controlled studies, fruits and vegetables were shown to have a favorable effect on several risk factors, including: blood pressure, lipid concentration, insulin resistance, inflammatory biomarker concentrations, endothelial function, and weight control [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of an unhealthy dietary pattern, this may have an effect on increased blood sugar, LDL-cholesterol and triglycerides. Thus, poor diet contributes to the occurrence of a cluster of disorders known as the metabolic syndrome: abdominal obesity, hypertension, dyslipidemia, and disturbed metabolism of glucose or insulin [42]. The presence of the metabolic syndrome increases the risk of developing NCDs such as cardiovascular diseases, diabetes, chronic respiratory diseases, and cancer [43,44].…”
Section: Discussionmentioning
confidence: 99%